Six-month survival benefits associated with clinical guideline recommendations in acute coronary syndromes. Issue 15 (7th June 2010) - Chew, D P; Anderson, F A; Avezum, Á; Eagle, K A; FitzGerald, G; Gore, J M; Dedrick, R; Brieger, D; ,
Abstract : Aims: The authors sought to define which guideline-advocated therapies are associated with the greatest benefit with respect to 6-month survival in patients hospitalised with an acute coronary syndrome (ACS). Methods and results: The authors conducted a nested case–control study of ACS patients within the Global Registry of Acute Coronary Events cohort between April 1999 and December 2007. The cases were ACS patients who survived to discharge but died within 6 months. The controls were patients who survived to 6 months, matched for ACS diagnosis, age and the Global Registry of Acute Coronary Events risk score. Rates of use of evidence-based medications and coronary interventions (angiography, percutaneous coronary intervention and coronary artery bypass graft surgery) were compared. Logistic regression including matched variables was used, and the attributable mortality from incomplete application of each therapy was calculated. A total of 1716 cases and 3432 controls were identified. Coronary artery bypass graft surgery and percutaneous coronary intervention were associated with the greatest 6-month survival benefit (OR for death 0.60 (95% CI 0.39 to 0.90) and 0.57 (0.48 to 0.72), respectively). Statins and clopidogrel provided the greatest independent pharmacologic benefit (ORs for death 0.85 (0.73 to 0.99) and 0.84 (0.72 to 0.99)) with lesser effects seen with other pharmacotherapies. Conclusions: A diminishing benefit associated with each additional ACS therapy is evident. These data may provide a rational basis for selecting between therapeutic options when compliance or cost is an issue.